New Frontiers in Social Innovation Research. - Nicholls, Alex. (Palgrave Macmillan UK, 2015)
This book is open access under a CC BY license. Interest in social innovation is growing, yet theory lags behind practice. This collection helps bridge that gap, compiling work by leading social innovation researchers to build understanding of the nature and effects of social innovation.